A case of adult-onset Still’s disease accompanied with pulmonary tuberculosis successfully treated with colchicine - Rao, Shijia; Shi, Wei (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2021)
A 54-year-old man admitted to our department presented with recurrent fever for 18 months with arthralgia and skin rash in May 2018. The patient appeared to have run a fever with no obvious cause since December 2016. His highest body temperature was 41°C, accompanied by arthralgia and myalgia, the laboratory examination showed the following: white blood cells (WBC) 12.59 × 109/l (3.5–9.5 × 109/l) with neutrophils 75.3% (40–75%); C-reactive protein (CRP) 65.8 mg/l (0–8 mg/l), erythrocyte sedimentation rate (ESR) 87 mm/h (0–15 mm/h), negative for cytomegalovirus (CMV), EBV-DNA, TORCH, ANA, ds-DNA, SSA, SSB, anti-Sm, RF, ANCA, mycoplasma, and chlamydia. Procalcitonin (PCT) 0.11 ng/ml (< 0.05 ng/ml). Pulmonary computed tomography (CT) showed nodules and chordal shadows in the right upper lung with partial calcification and mediastinal lymphadenopathy. T-spot result showed 247.4 pg/ml (< 14 pg/ml), but was negative for acid-fast staining of sputum. The patient had been in remission from pulmonary tuberculosis history for 30 years.